Bone marrow analysis of immune cells and apoptosis in patients with systemic lupus erythematosus. (September 2014) - Park, JW; Moon, SY; Lee, JH; Park, JK; Lee, DS; Jung, KC; Song, YW; Lee, EB
Objectives: To examine the immune cell profile in the bone marrow of systemic lupus erythematosus (SLE) patients and to assess its clinical relevance. Methods: Sixteen bone marrow samples from 14 SLE patients were compared with seven healthy control samples. The numbers of immune cells and apoptotic cells in the bone marrow were examined by immunohistochemistry. The association between immune cell subsets and clinical features was investigated. Results: CD4+ T cells, macrophages and plasma cells were more common in the bone marrow of SLE patients than in healthy controls ( p =  0.001, p =  0.004 and p  < 0.001, respectively). Greater numbers of CD4+ T cells and macrophages were associated with high-grade bone marrow damage. The percentage of apoptotic cells in bone marrow of SLE patients was significantly higher than that in controls ( p  < 0.001) and was positively correlated with the number of plasmacytoid dendritic cells ( p =  0.013). Increased number of plasma cells along with high interleukin-6 expression was correlated with anti-double stranded DNA antibody levels and the SLE disease activity index ( p =  0.031 and 0.013, respectively). Conclusion: Bone marrow from SLE patients showed a distinct immune cell profile and increased apoptosis. This, coupled with a correlation with disease activity, suggests that the bone marrow may play a critical role in the pathogenesis of SLE.